INSTITUTIONALISED INDIGENOUS KNOWLEDGE AS A FOUNDATIONAL ELEMENT OF RURAL-BASED SUSTAINABLE DEVELOPMENT GOAL IN OLEHSARI VILLAGE BANYUWANGI - Hidayati, Emi; Septalinda, Ficky; Fardian, M. Iqbal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study research aims to uncover how the Osing people's indigenous knowledge can contribute to preserving water resources in Olehsari Village, Glagah Sub-district, Banyuwangi. Indigenous knowledge encompasses various cultural, ecological, and epistemological frameworks essential for understanding and addressing today's concerns, particularly sustainable development goals. It is increasingly acknowledged that advancing social justice, cultural identity, and sustainability requires integrating Indigenous knowledge into various fields.   It is widely accepted that incorporating Indigenous knowledge into a broad spectrum of fields is critical to fostering social justice, cultural identity, and sustainability. Efforts to commercialize community-owned resources, notably water resources, pose a significant danger to Kemiren Banyuwangi Village's Indigenous Knowledge, a critical pillar for natural resource preservation for decades.   The village government's commercialization initiatives through Bumdes will undoubtedly alter the community's Indigenous knowledge, which has been demonstrated to be a critical pillar for the long-term sustainability of water supplies and village residents' lifestyles. This study used descriptive qualitative methodologies, with data collected through documentation, in-depth interviews, and observation. According to the study's findings, indigenous knowledge in sustainable village development has increased dramatically to improve community well-being and environmental sustainability, which face considerable problems. When Indigenous knowledge is compromised, water resources, farming, and the community as a whole are threatened. Sustainable agricultural practices will fail due to a growth-based development paradigm that disregards Indigenous Knowledge, particularly in meeting the United Nations' Sustainable Development Goals (SDGs). Incorporating indigenous and local knowledge into farming systems is a critical strategy for achieving SDG2, which is intended to eradicate hunger and enhance sustainable agriculture.